Urbanism, Architecture and Modern Urban Development - Hakimi, Hossein; Yari Firoozabadi, Sajjad (European Journal of Sustainable Development, 2018)
Developing countries are subject to quick cultural changes as they evolve. Modern cities have been constructed by the interactions between different types of subjects. The identities of the actors that have been altered by communication in different forms of systems need new structures and infrastructures. The infrastructures should be in alignment with this evolving situation. The substructure is one of the objective reasons for the communication of citizens as, in this regard, individuals (citizens) will experience more emotional enjoyment from the freedom based on the number of facilities available to them. As with both objective and subjective discourses, the city will become more prominent in the modernized architectural structures if it is within the subjective scope of the citizens? free choices. To survive in this vibrant era, architecture has no choice but to be combined with the technologies derived from the modern science. Therefore, if technology or architecture is one of the options available to the citizens of metropolitan cities, it will create small communities and places due to its discursive nature and its locality and amusing quality where the citizen and city are placed in a dynamic situation as an actor and substructure. Our approach in this article has been scientific research and the impact of technology-architecture on modern urban development is studied based on the views of George Simmel and the city?s dependence on the architecture which has derived from this notion. Keywords: Interaction, architecture, city and modern urban development, citizenship, infrastructure, technology